2015
DOI: 10.1016/j.physbeh.2015.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Male adolescent rats display blunted cytokine responses in the CNS after acute ethanol or lipopolysaccharide exposure

Abstract: Alcohol induces widespread changes in cytokine expression, with recent data from our laboratory having demonstrated that, during acute ethanol intoxication, adult rats exhibit consistent increases in interleukin (IL)-6 mRNA expression in several brain regions, while showing reductions in IL-1 and TNFα expression. Given evidence indicating that adolescence may be an ontogenetic period in which some neuroimmune processes and cells may not yet have fully matured, the purpose of the current experiments was to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
93
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 69 publications
7
93
0
Order By: Relevance
“…Consistent with this, the present data show that IκBα expression was positively correlated with IL-6 (r = 0.86), whereas the relationship of IκBα to both TNFα and IL-1β was not significant (r = 0.02, 0.03 respectively). This intriguing finding suggests a significant departure from the simple expectation that NF-κB signaling (reported by increased IκBα gene expression) would show a strong positive correlation with all 3 of these cytokines, and is consistent with our previous work examining acute ethanol effects (Doremus-Fitzwater et al, 2015). Based on our present data, therefore, future studies examining more specific features of NF-κB signaling are of high priority for elucidating the seemingly paradoxical dissociation between IκBα and TNF/IL-1β.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with this, the present data show that IκBα expression was positively correlated with IL-6 (r = 0.86), whereas the relationship of IκBα to both TNFα and IL-1β was not significant (r = 0.02, 0.03 respectively). This intriguing finding suggests a significant departure from the simple expectation that NF-κB signaling (reported by increased IκBα gene expression) would show a strong positive correlation with all 3 of these cytokines, and is consistent with our previous work examining acute ethanol effects (Doremus-Fitzwater et al, 2015). Based on our present data, therefore, future studies examining more specific features of NF-κB signaling are of high priority for elucidating the seemingly paradoxical dissociation between IκBα and TNF/IL-1β.…”
Section: Discussionsupporting
confidence: 89%
“…More recently, data from our own laboratory has shown that acute ethanol administration (4 g/kg) elicits a robust and significant elevation in IL-6 and nuclear factor of kappa light polypeptide gene enhancer in B-cells inhibitor, alpha (IκBα) gene expression in the hippocampus, paraventricular nucleus of the hypothalamus (PVN) and amygdala during acute intoxication (i.e., 3 h after exposure), whereas IL-1β and TNFα tend to be suppressed during intoxication in most structures (Doremus-Fitzwater et al, 2014, 2015). For convenience, we now refer to these highly reproducible cytokine changes observed during acute intoxication (increased IL-6 and IκBα, decreased IL-1β and TNFα) as Rapid Alterations in Neuroimmune Gene Expression (RANGE) effects.…”
Section: Introductionmentioning
confidence: 99%
“…HSP-3805) and the reaction was captured in real-time with a PCR detection system (BioRad, Model No. CFX384) (Doremus-Fitzwater et al, 2015). The first step in the PCR reaction was a 3-min hot start (95° C), followed by denaturation (30 s at 95° C), annealing (30 s at 60° C), and finally an extension step (30 s at 72° C) for 50 cycles.…”
Section: 0 Experimental Proceduresmentioning
confidence: 99%
“…Thus, results from this model are likely to be most relevant to alcohol use that starts in the juvenile or adolescent stage of life, a pattern of alcohol use that has significant risk for developing alcohol dependence and is currently an important societal issue (Foltran et al, 2011; Hingson et al, 2006). Studies in animal models have shown that ethanol exposure increases IL-6 levels in the CNS of adolescents as well as adults (Doremus-Fitzwater et al, 2015). …”
Section: Introductionmentioning
confidence: 99%